2013
DOI: 10.1007/s13277-013-1256-3
|View full text |Cite
|
Sign up to set email alerts
|

XPD Asp312Asn and Lys751Gln polymorphisms and breast cancer susceptibility: A meta-analysis

Abstract: The association between xeroderma pigmentosum complementation group D (XPD) Asp312Asn and Lys751Gln gene polymorphisms and breast cancer risk has been widely reported, but the results were inconsistent. In order to derive a more precise estimation of the relationship, a meta-analysis was performed. A comprehensive search strategy was conducted towards the electronic databases including Medline, PubMed, Web of Science, Embase, and Chinese Biomedical Literature Database (Chinese). The association between the XPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…Previous studies have demonstrated that a defect of the DNA repair function is a risk factor for several kinds of cancer, including bladder cancer, acute leukemia, and breast cancer (Yan et al, 2014;Liu et al, 2014). reported a meta-analysis with 11 studies, including 3797 cases and 5094 controls, and showed that polymorphism in ERCC2 rs13181 contributes to bladder cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that a defect of the DNA repair function is a risk factor for several kinds of cancer, including bladder cancer, acute leukemia, and breast cancer (Yan et al, 2014;Liu et al, 2014). reported a meta-analysis with 11 studies, including 3797 cases and 5094 controls, and showed that polymorphism in ERCC2 rs13181 contributes to bladder cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…reported a meta-analysis with 11 studies, including 3797 cases and 5094 controls, and showed that polymorphism in ERCC2 rs13181 contributes to bladder cancer susceptibility. Yan et al (2014) conducted a meta-analysis with 22 studies, and reported that polymorphism in ERCC2 rs13181 significantly increased breast cancer risk. Liu et al (2014) performed a meta-analysis with ten published case-control studies including 1494 cases and 2259 controls, and reported that the ERCC2 rs13181 variant genotype might be a risk factor for acute leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, three newly updated meta-analyses revealed that there were no evidence supporting that XPD Lys751Gln polymorphism contributed to prostate cancer (Ma et al, 2013) , colorectal cancer (Zhang et al, 2011) , or gastric cancer (Yin et al, 2013). On the contrary, other large sample meta-analyses proposed a greater risk in hepatocellular carcinoma (Guo et al, 2012), breast cancer (Yan et al, 2014), lung cancer , glioma (Chen et al, 2012), and acute myeloid leukemia (AML) (Liu et al, 2014). For XPD Asp312Asn polymorphism, three meta-analyses proposed a greater risk in prostate cancer (Ma et al, 2013), gastric cancer (Yin et al, 2013), and esophageal cancer (Duan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For XPD Asp312Asn polymorphism, three meta-analyses proposed a greater risk in prostate cancer (Ma et al, 2013), gastric cancer (Yin et al, 2013), and esophageal cancer (Duan et al, 2012). However, other large sample meta-analyses showed that it did not contribute to breast cancer (Yan et al, 2014), lung cancer , colorectal cancer (Zhang et al, 2011) or head and neck cancer (Hu et al, 2012) risk.…”
Section: Discussionmentioning
confidence: 99%
“…Asp312Asn and Lys751Gln polymorphisms are the two most widely investigated ERCC2 polymorphisms associated with increased DNA adduct levels and with low DNA repair capacity (Lunn et al, 2000), which suggests that these two SNPs may contribute to carcinogenesis and can be regarded as risk factors for cancer development. Recently, many systematic reviews and meta-analyses have been performed to examine the association of ERCC2 polymorphisms with various cancers (Duan et al, 2012;Yin et al, 2013;Huang et al, 2014;Liu et al, 2014;Xin et al, 2014;Yan et al, 2014;Zhu et al, 2014) except for NHL. What's more, epidemiological studies investigating the association of ERCC2 polymorphisms with NHL risk in populations of different ethnic origin have been published, but the results remain inconclusive (Shen et al, 2006;Smedby et al, 2006;Shen et al, 2007;Song et al, 2008;Baris et al, 2009;Worrillow et al, 2009;Yang et al, 2009;El-Din et al, 2013;Fabisiewicz et al, 2013;Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%